Zinc K‐edge XANES spectroscopy of mineral and organic standards. (21st June 2019) - Castorina, Erin; Ingall, Ellery D.; Morton, Peter L.; Tavakoli, David A.; Lai, Barry
Abstract : Zinc K ‐edge XANES reference standards of zinc mineral samples and organic compounds are presented. Abstract : Zinc K ‐edge X‐ray absorption near‐edge (XANES) spectroscopy was conducted on 40 zinc mineral samples and organic compounds. The K ‐edge position varied from 9660.5 to 9666.0 eV and a variety of distinctive peaks at higher post‐edge energies were exhibited by the materials. Zinc is in the +2 oxidation state in all analyzed materials, thus the variations in edge position and post‐edge features reflect changes in zinc coordination. For some minerals, multiple specimens from different localities as well as pure forms from chemical supply companies were examined. These specimens had nearly identical K ‐edge and post‐edge peak positions with only minor variation in the intensity of the post‐edge peaks. This suggests that typical compositional variations in natural materials do not strongly affect spectral characteristics. Organic zinc compounds also exhibited a range of edge positions and post‐edge features; however, organic compounds with similar zinc coordination structures had nearly identical spectra. Zinc XANES spectral patterns will allow identification of unknown zinc‐containing minerals and organic phases in future studies.